Qualidade de queijos produzidos no estado da Paraíba: adequação da legislação, composição físico-química e perfil lipídico - Matias, Suéllen Maria Gonçalves (2014)
Cheeses are highlighted among milk derivatives due of their nutritional value with high protein and fat content. Labeling of cheeses, as well as any packaged food manufacturing, is inspected under the designations of quality seal from the Federal Inspection Service (SIF) or State (SIE) that act in accordance with the regulations arranged in RDC 259, of September 20th, 2002 and RDC 360, December 23th, 2003, ensuring the marketing adequate of products with nutritional quality. The aim of this study was analyze the adequacy of labeling, physico-chemical composition and lipid profile of different types of commercial cheeses produced in Paraíba. We evaluated a total of 42 samples of cheeses made with different technologies (coalho, butter and ricotta), containing seals of State and Federal Inspection, collected in local supermarkets. Through a check list according to current laws, the labels were evaluated in aspects of packaging, processing and nutritional (moisture, total solids, fat, protein, saturated fatty acids and Conjugated Linoleic Acid (CLA). The study revealed that 85.7 % of the labels do not comply with current legislation, highlighting the technological aspects like the indication of durability after opening the package (57.1%) and way of conservation (42.8 %). Differences were found in the concentrations of total solids, fat and moisture between cheeses with different technologies, focusing on coalho and butter cheeses as high humidity (up 54.9 %), in accordance with specific technical regulations. The amounts of protein, unsaturated fatty acids and CLA didn t differ between the types of cheese, however, as the seals of inspection, samples showed variations in relation to the protein content. Considering the lack of conformity of labels and standardization of the technology for cheeses produced in Paraíba, it turns out the need for public policies and better supervising of labeling has been applied to consolidate recovery, support the process of identifying and recognizing regional products such as cheeses of this study.